Wartość poznawcza gotówkowej wartości dodanej (CVA) w ocenie wypłacalności przedsiębiorstw - Mioduchowska-Jaroszewicz, Edyta (Use CVA in Estimation Solvency Enterprises, 2005)
Methodology estimation solvency enterprise should be simply, comprehensible and coherent ex post and ex ante. Measure to live this aspects is CVA. Estimation this 13 enterprises CVA give abilities analysis solvency. Estimation CVA point to realize strategy, which doesn't assure you keep solvency.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1061, s. 268-275